2005
DOI: 10.1063/1.1856480
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Raman scattering of relativistic laser beam in plasmas

Abstract: This paper presents the stimulated Raman scattering (SRS) of relativistic laser beam in unmagnetized plasma. The effect of the relativistic electron mass nonlinearity and the relativistic self-focusing of the pump laser on the SRS process is studied. The effect of nonlinear coupling between the pump laser and scattered laser beam has been incorporated. Semianalytical solution for the back reflectivity for SRS has been obtained. For a typical laser wavelength (λ0=1.053μm), intensity (1018Wcm−2), and a plasma ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…[25][26][27][28][29][30] Most of the studies related to filamentation and SRBS instability have been reported by taking in to account separately the relativistic or ponderomotive nonlinearity. However, in actual case when high power laser beam propagates in plasma, both relativistic and ponderomotive nonlinearities simultaneously arise depending on the time scale of the pulse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29][30] Most of the studies related to filamentation and SRBS instability have been reported by taking in to account separately the relativistic or ponderomotive nonlinearity. However, in actual case when high power laser beam propagates in plasma, both relativistic and ponderomotive nonlinearities simultaneously arise depending on the time scale of the pulse.…”
Section: Introductionmentioning
confidence: 99%
“…The study of enhanced Raman scattering of a rippled laser beam in magnetized collisional plasma has also been reported by Saini and Gill 35 and observed that the Raman scattering in plasma is enhanced due to strong coupling between main beam, ripple, and excited electron plasma wave. Salih et al 25 have investigated the stimulated Raman scattering of relativistic laser beam in underdense plasma for both paraxial laser beam and extended beam. The effect of relativistic and ponderomotive nonlinearities on stimulated Raman scattering process in unmagnetized plasma has also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] have examined laser-plasma instabilities excited by short and intense laser pulses. However in these works [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] studying shaped pulses, the wide use of SVEA makes the effect of pulse shape on various instabilities difficult to estimate exactly. When a short and intense laser pulse interacts with plasmas, the high intensity will cause various relativistic effects important to the phase matching condition, which is very crucial for the multiwave process.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the slow-varying envelope approximation ͑SVEA͒ is widely applied in many investigations of the interaction of shaped pulses with plasmas. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] It requires expertise to successfully apply SVEA in a situation of varying envelopes of the laser pulse. Because recently more research interest has focused on the interaction of plasmas with short laser pulse whose envelope variation is obvious, it is necessary to develop the relevant theory beyond the slow-varying envelope approximation.…”
Section: Introductionmentioning
confidence: 99%
“…In papers [8,9,10] the laser intensity I = 10 22 W m −2 is considered. In the papers [11] and [12] authors mention that the construction of lasers with the laser intensity I = 10 22 ÷ 10 24 W m −2 is done.…”
Section: Introductionmentioning
confidence: 99%